Exposure to Hedione Increases Reciprocity in Humans - Berger, Sebastian; Hatt, Hanns; Ockenfels, Axel (Frontiers in Behavioral Neuroscience, 2017)
Cooperation among unrelated humans is frequently regarded as a defining feature in the evolutionary success of our species. Whereas much research has addressed the strategic and cognitive mechanisms that underlie cooperation, investigations into chemosensory processes have received very limited research attention. To bridge that gap, we build on recent research that has identified the chemically synthesized odorant Hedione (HED) as a ligand for the putative human pheromone receptor (VN1R1) expressed in the olfactory mucosa, and hypothesize that exposure to HED may increase reciprocity. Applying behavioral economics paradigms, the present research shows that exposure to the ligand causes differentiated behavioral effects in reciprocal punishments (Study 1) as well as rewards (Study 2), two types of behaviors that are frequently regarded as essential for the development and maintenance of cooperation.